THE INTERNAL COMMUNICATION IN HOTEL FRONT OFFICE DEPARTMENT - Fakhri, Muhammad Reza; Marini, Sri (Universitas Pendidikan Indonesia, 2019)
This study aimed to find out the internal communication of front office department at Kytos Hotel Bandung. Communication is the important key in directing and coordinating of establishment. Poor communication of front office department will be impact to customer satisfaction and will decrease the revenue of the hotel. Problems arised in this research: 1) 1. How is the downward communication of front office department at Kytos Hotel Bandung?; 2) How is upward communication of front office department at Kytos Hotel Bandung?; and 3) How is horizontal communication of front office department at Kytos Hotel Bandung. The purpose of this research is to find out the downward communication, upward communication and horizontal communication of front office department at Kytos Hotel Bandung. The method used is a quantitative method. Observation, interviews, documentation, and questionnaires are used as a technique data collection. While the data analysis technique uses a Likert scale. Based on the results of the study, it can be seen that vertical communication (upward communication and downward communication) and horizontal communication performed by front office department at Kytos Hotel Bandung are still in the less category.